Maternal and Neonatal Characteristics and its Contact Tracing of Covid-19 in Pregnancy in Cipto Mangunkusumo General Hospital - Junita Indarti; Handika Zulimartin; Boeyoeng E.A.P Dalimunte; Nova V. Wijaya; Henny S. Wonodihardjo; Ario B. Hanggono; Kristian Alda; Mohammad A.F Dilmy; Siti R.F Harun (Faculty of Medicine Universitas Indonesia, 2022)
Pregnant women might be at greater risk for common pregnancy complications and baby abnormalities if they are infected with COVID-19. This cross-sectional study aims to investigate the characteristics of pregnant women with COVID-19, using secondary data from medical records of subjects treated with COVID-19 at Cipto Mangunkusumo Hospital from January to June 2021. 102 pregnant women with confirmed COVID-19 were enrolled and 77 were delivered during admission. Enrolled subjects mostly consisted of multigravidas 58 (56.8%) between 29-36 weeks gestation 42 (41.1%). No comorbidities were present in the majority of subjects that were enrolled. Most presented with mild symptoms 50 (49%) and 21 (20,6%) with moderate symptoms. Most were delivered by Caesarean section (CS) a total of 58 out of 102 cases (75.4%). A total of 8 (7.9%) of those with severe cases with acute respiratory distress syndrome were admitted to intensive care. Pulmonary consolidation corresponding to pneumonia on chest x-ray were findings in 43 (42.2%) women. The majority of neonates born 36 (37.1%) had a birth weight of 1500-2499 grams. The were no positive COVID-19 findings of neonatal nasopharyngeal swab results. Perinatal complications occurred in 28 (36.3%) neonates that experienced respiratory distress and 22 (28.6%) experienced neonatal sepsis. A total of 44 (57.1%) infants with birth weight <2500 grams. Among these neonates 41 (55.4%) required NICU admission, 10 (13.5%) required ventilators due to respiratory distress. Most of the subjects on contact tracing, contracted COVID-19 from their neighbors or close relatives; 56(54.9%). There was 1 case of maternal death. In addition, we found that most of COVID-19 transmissions originated from asymptomatic close relatives and neighbors.